All meromorphic solutions of an ordinary differential equation and its applications. (18th February 2016) - Yuan, Wenjun; Meng, Fanning; Lin, Jianming; Wu, Yonghong
Abstract : Dedicated to Professor Yuzan He on the Occasion of his 80th Birthday In this paper, we employ the complex method to obtain all meromorphic solutions of an auxiliary ordinary differential equation at first and then find out all meromorphic exact solutions of the combined KdV–mKdV equation and variant Boussinesq equations. Our result shows that all rational and simply periodic exact solutions of the combined KdV–mKdV equation and variant Boussinesq equations are solitary wave solutions, the method is more simple than other methods, and there exist some rational solutions w r, 2 ( z ) and simply periodic solutions w s, 2 ( z ) that are not only new but also not degenerated successively by the elliptic function solutions. Copyright © 2016 John Wiley & Sons, Ltd.